EFFECTIVENESS OF INTERCROPPING ON SOIL BORNE PESTS INFESTATION IN POTATO - B. KAHAR (The Journal of Research ANGRAU, 2023)
Bio-efficacy of different treatment schedules of intercropping, viz., T1 (potato+onion), T2 (potato+garlic), T3 (potato+tomato), T4 (potato+coriander), T5 (potato+radish), T6 (control) and T7 (recommended insecticide) were evaluated against cutworm, Agrotis ipsilon (Hufner), mole cricket, Gryllotalpa africana, P.de. Beau. and potato tuber moth (PTM), Phthorimaea operculella (Zeller) with potato variety ‘Kufri Jyoti’ during rabi season of 2017- 2018 and 2018-2019 (November to February). A great deal of variation in the incidence of potato tuber damaging soil pests was observed with different intercrops. Among the different intercropping systems, tuber damage caused by different soil pests was maximum when intercropped with tomato (T3) and minimum with onion (T1) and garlic (T2), respectively. However, intercropping method was not as effective as recommended insecticide (T7) in reducing soil pest incidence on potato.